Strategic Entrepreneurship and Performance of Small and Medium Scale Enterprises in Aba Metropolis - Makinde, Olubisi Grace; Agu, Carolyn Ugochi (Archives of Business Research, 2018)
Strategic entrepreneurship has become dominant in the contemporary world and it is considered an effective tool for economic. Small and medium scale enterprises (SMEs) in Aba metropolis are faced with issues like inadequate information about strategic entrepreneurship, low entrepreneurial innovation which had resulted into low productivity and inefficiency in profit maximization. Little attention have been given into how strategic entrepreneurship contributes to performance of SMEs in Aba metropolis, Abia State. This study examined the effect of strategic entrepreneurship on performance of selected SMEs in Aba metropolis. The study adopted the survey research design. The population of the study consisted of 231 owner/managers of the selected SMEs in the manufacturing, the finance, health and the food and beverages sectors in Aba metropolis. The total enumeration method of sampling was used and data were gathered through the use of a questionnaire. The instrument was validated and the KMO values were greater that 0.5 while the reliability test was 0.875. Data were analyzed using simple linear regression analysis. The results revealed that strategic entrepreneurship variables have effects on the performance variables. The study concluded that strategic entrepreneurship plays an important role in enhancing the performance of SMEs in Aba metropolis. It was therefore recommended that SMEs should pay critical attention to the adoption of strategic entrepreneurship due to its positive effect on performance.